WEB BASED LIBRARY SYSTEM OF SMKN 8 BANDUNG - Andhika Dwi Syahputra; Ari Purno Wahyu Wibowo (JURNAL DARMA AGUNG, 2022)
Data collection is generally done manually, but this has drawbacks, namely that the archive becomes disorganized, and searching for data takes quite a lot of time. Likewise with library management at SMKN 8 Bandung, data collection is still manual so there are often many mistakes. For this reason, it is necessary to have a web-based library information system where data management will be more organized. The research method used is Research and Development (R&D) with the Extreme development method Programming . Methods of data collection using observation, interviews, and literature study. The interview method is used to determine user needs, a questionnaire questionnaire is used to test the feasibility of the usability aspect , while the observation is for testing the performance aspect. efficiency . The result of this research is a web - based library information system using PHP language and MySQL database server . The test results proved that the level of feasibility of a web-based library information system in the usability aspect of small groups with very feasible criteria.